Clinical and laboratory profile of hospitalized patients affected by pressure injury (Estima – Brazilian Journal of Enterostomal Therapy, 2020)
Objective: To characterize the clinical and laboratory profile of hospitalized patients affected by pressure injury (PI). Method: Retrospective and descriptive study, which included data from electronic medical records of 95 patients affected by PI during hospitalization. Results: There was a predominance of females (52.6%), mean age 74.8 ± 14 years, mean hospital stay was 76.9 ± 88.8 days. Most were admitted to the intensive care unit, with an average of 17.86 ± 36.58 days. Regarding the clinical condition, 60% were using a mechanical ventilator when they developed PI, 37.9% needed hemodialysis, 30.4% were diagnosed with some degree of protein-energy malnutrition and 54.7% progressed to death. The most frequent comorbidities were hypertension (63.16%), diabetes (43.16%) and neuropathy (33.68%). As for the laboratory profile, hypoalbuminemia (97.3%), hyperglycemia (87.8%), anemia (84.4%) and hyperuremia (78.9%) were present in more than two thirds of the sample. Conclusion: This study allowed to know the profile of patients affected by PI during hospitalization, which can serve as a basis for developing scientifically based effective preventive actions.